2016
DOI: 10.1021/acs.jpca.6b07242
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Optical Properties of Boron Difluoride Dibenzoylmethane Derivatives

Abstract: Electronic structure and optical properties of boron difluoride dibenzoylmethanate BF2Dbm and its four derivatives were studied using X-ray photoelectron spectroscopy, absorption and luminescence spectroscopy, and quantum chemistry (DFT and TDDFT). In a series of the studied compounds, the relationship of molecular design and optical properties has been revealed. At the transition from BF2Dbm to BF2Dbm(OCH3)2, the HOMO-LUMO energy gap decreases, resulting in a bathochromic shift of the optical spectra. Substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 45 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…A similar process allows obtaining boranil derivatives (Figure b). , However, in that event the proton of an OH group is substituted in the last step of the synthetic route leading to a N–B–O type linkage. Yet another class of compounds with BF 2 moiety are diketonates (Figure c) that also constitute an increasingly popular family, whereas diiminates (with BF 2 bonded to two nitrogen atoms) (Figure d) as well as ketoiminates (Figure e) with unsymmetrically bonded BF 2 moiety have also been studied. Globally, the BF 2 -carrying molecules are the most popular organic fluorophores to date and, as Ziessel pointed out, they constitute an “El Dorado for fluorescence tools” .…”
Section: Introductionmentioning
confidence: 99%
“…A similar process allows obtaining boranil derivatives (Figure b). , However, in that event the proton of an OH group is substituted in the last step of the synthetic route leading to a N–B–O type linkage. Yet another class of compounds with BF 2 moiety are diketonates (Figure c) that also constitute an increasingly popular family, whereas diiminates (with BF 2 bonded to two nitrogen atoms) (Figure d) as well as ketoiminates (Figure e) with unsymmetrically bonded BF 2 moiety have also been studied. Globally, the BF 2 -carrying molecules are the most popular organic fluorophores to date and, as Ziessel pointed out, they constitute an “El Dorado for fluorescence tools” .…”
Section: Introductionmentioning
confidence: 99%
“…32 In a computational study, Mirochnik et al used alkoxy donors to change the energy level of the HOMO and nitro-accepting groups to adjust the energy level of the LUMO in BF 2 dbm complexes, where greater red shift in emission resulted from para-substituted nitro acceptors in BF 2 dbm. 33 A decrease in the HOMO−LUMO energy gap with para-substituted accepting groups is also achieved with halide substitution. 34 Typically, para-substituted ketone and ester building blocks are employed in β-diketonate ligand synthesis, which results in π−π* absorption in the corresponding boron dibenzoylmethane dyes.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Cano et al studied asymmetric alkoxy substitution on both aryl moieties of difluoroboron dibenzoylmethane complexes and found that the asymmetric substitution pattern yielded compounds with larger Stokes shifts and longer emission lifetimes. , Kononevich et al studied alkoxysilyl derivatives of BF 2 dbm and showed that para- and meta-substitution of alkoxysilyl groups resulted in compounds with higher quantum yields and more red-shifted emission compared to ortho -alkoxysilyl substitution . In a computational study, Mirochnik et al used alkoxy donors to change the energy level of the HOMO and nitro-accepting groups to adjust the energy level of the LUMO in BF 2 dbm complexes, where greater red shift in emission resulted from para-substituted nitro acceptors in BF 2 dbm . A decrease in the HOMO–LUMO energy gap with para-substituted accepting groups is also achieved with halide substitution …”
Section: Introductionmentioning
confidence: 99%